Penggunaan Tepung Limbah Udang yang Diolah dengan Filtrat Air Abu Sekam dalam Ransum Ayam Broiler - . Mirzah (Media Peternakan, 2007)
The objective of this study was to measure the effect of different levels of shrimp head waste (SHW) substituting fish meal (FM) in broiler diets. FM is the sole crude protein from animal sources. A control fish meal broiler diet and four different levels of SHW substituted for crude protein FM were fed to CP 707 Arbor Acres broiler strains from day old chick to four weeks of age. The crude proteins FM were replaced with 0 (R0); 25 (R1); 50 (R2); 75 (R3); and 100 (R4) percent of crude protein SHW. The five treatments were assigned to completely randomized design. Feed consumption, body weight gain, feed conversion and carcass percentage were recorded to measure the performances. The results of Duncan's revealed that feed consumption, feed conversion and carcass percentage were not significantly different with increasing level of SHW as substituted crude protein FM in broiler diets. However these parameters in bird fed 100 % SHW diets did not differ from those in birds fed 16 % FM (7.32% crude protein from FM). While body weight gain decreased with increasing levels of SHW in broiler diets (R4). The decrease body weight gain may be due to the decreased feed intake and amino acid in balance and the increased chitin content in the diet. The conclusion of this experiment that SHW can be used as a protein source in broiler diets up to 75% to replace FM. Key words: shrimp head waste meal, fish meal, broiler, performances